Pengujian Optimization dan Non-Optimization Query Metode Topsis untuk Menentukan Tingkat Kerusakan Sektor Bencana Alam - Safitri, Annisa Heparyanti; Almais, Agung Teguh Wibowo; Syauqi, A'la; Melani, Roro Inda (P3M Politeknik Negeri Banjarmasin, 2022)
The huge volume of data from the Disaster Management Planning and Control (P3B) surveyor team creates wide and varied problems that can consume system resources and processing time that is relatively long. There-fore, this study proposes a solution by performing query optimization on the TOPSIS method which is implemented in a decision support system to determine the level of post-disaster damage. Based on 3 trials with different amounts of data, the 1st trial used 114 data, the 2nd trial used 228 data and the 3rd trial used 334 data. In addition, for each trial, the response time measurement was repeated 3 times, so that the average response time of each step of the TOPSIS method was obtained. It was found that the results of the ranking stage using query optimization were 0.00076 faster than the non-optimization query. So, it can be concluded that the response time obtained by query optimization at each step of the TOPSIS method in the post-natural disaster sector damage decision support system is smaller than the response time in non-optimization queries.